Growth empirics: Structural transformation and sectoral interdependencies of Sri Lanka - S. P. Jayasooriya (Asian Development Bank Institute (ADBI), 2017)
Even though the impacts of the globalization on economic growth and structural changes are inevitable, many developing countries are slowly transformed in the process. This paper examines the impact of structural transformation of Sri Lanka's economy on sectoral interdependencies to provide evidence for policy making. It advocates policies, investigating the relationship among agricultural, industrial, and service-related gross domestic products (GDPs) under (i) an open economic policy setting, (ii) different government policy regimes, and (iii) major policy eras from 1950 to 2015. The analysis uses secondary data from the Central Bank of Sri Lanka and the Institute of Policy Studies publications. A time-series econometric method, vector autoregression, was used including causality analysis, and Gregory-Hansen cointegration, for estimating a long-run relationship in sectoral growth. The empirical investigations revealed an existence of unidirectional causality toward agricultural to industrial GDP, and bidirectional causality between agricultural and service GDPs in terms of Sri Lanka's economy. The effect of Gregory-Hansen co-integration affirmed a long-run nexus in agricultural growth positively with industrial and service growth. Apart from that, the evidence of structural change through open economic policies depicted a significant impact between pre-open economic and post-open economic policies for a drastic economic growth even under structural break. Although none of the policy regimes have prejudiced economic growth, reforms can be initiated to ascertain the revival of economic growth, and promoting service sector-related economic systems are desirable with reforming policies.
Keywords: C01; C22; H50; O11; Q18; Q28; 330; structural transformation; growth; open economy; vector autoregression; cointegration